2002
DOI: 10.1203/01.pdr.0000025347.92120.02
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Supplementation and Deprivation: Effect on Artificially Reared Rat Small Intestinal Morphology

Abstract: The mechanisms of how glutamine benefits critically ill patients have not been established. The purpose of this study was to determine the effects of dietary and endogenously produced glutamine on small intestinal morphology using light and transmission electron microscopy in artificially reared rat pups. It was hypothesized that deprivation of dietary glutamine leads to intestinal disease that is exacerbated by inhibition of glutamine synthetase by methionine sulfoximine (MS). Rat pups were placed into five d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
2
9
0
1
Order By: Relevance
“…[117] acid. Using a bacterial pathogenesis model of reared rats, Potsic et al [127] have shown the role of glutamine in the necrotizing enterocolitis in weanling rabbits, we have shown that maintenance of intestinal epithelial integrity. Instituting supplementation and deprivation in artificially necrotizing enterocolitis.…”
Section: Use Of Probiotics and Prebiotics To Promote A Healthysupporting
confidence: 51%
“…[117] acid. Using a bacterial pathogenesis model of reared rats, Potsic et al [127] have shown the role of glutamine in the necrotizing enterocolitis in weanling rabbits, we have shown that maintenance of intestinal epithelial integrity. Instituting supplementation and deprivation in artificially necrotizing enterocolitis.…”
Section: Use Of Probiotics and Prebiotics To Promote A Healthysupporting
confidence: 51%
“…However, daily protein intake at old ages should be higher because of the decrease in the ability of body for protein synthesis (1). Wound healing can be effected negatively in the presence of factors that increase collagen synthesis such as chronic malnutrition, diabetes mellitus, uraemia and advanced age (3,13). Therefore, in such cases, to increase wound healing, the requirement for the replacement of molecules like Gln, Arg and HMB that increase collagen synthesis cannot be denied.…”
Section: Discussionmentioning
confidence: 99%
“…For example, dietary supplementation with Gln can improve nutrition status in weanling piglets by preventing intestinal dysfunction and atrophy (Wang et al, ). Gln supplementation also has an effect on artificially reared rat small intestinal morphology, playing an important role in the maintenance of intestinal epithelial integrity (Potsic et al, ). Gln supplementation also affected the growth performance and small intestinal morphology of hatchling broilers, as a 1 g/kg Gln diet improved weight gain, feed efficiency and livability (Yi, Allee, Knight, & Dibner, ).…”
Section: Introductionmentioning
confidence: 99%